THE EFFECT OF WORK DISCIPLINE, JOB TRAINING, AND WORK MOTIVATION TO IMPROVE EMPLOYEES PRODUCTIVITY AT PT SUKSES ANUGRAH SEJAHTERA - Rezky, Raditia; Ani Murwani Muhar; Sarah Imelda (CV. Radja Publika, 2025)
This article explains the influence of work discipline, training, and motivation to increase employee productivity at PT. Sukses Anugrah Sejahtera (PT SAS). This article is compiled based on research conducted from March 2024 to September 2024. The research sample consisted of 108 PT SAS employees who worked in three locations, namely the University of North Sumatra, USU Hospital, and the Citra Garden complex with the type of work as Cleaning Service and Security. This type of research is quantitative using a saturated sampling technique. Primary data sources were obtained from respondents through questionnaires. Multiple linear regression analysis assisted by SPSS version 25 software was used to determine the relationship between the variables studied. The results of the study showed that work discipline, work training, and motivation simultaneously had a positive and significant effect on employee productivity at PT. Sukses Anugrah Sejahtera. In addition, partially the variables of work discipline, work training, and motivation each had a positive and significant effect on work productivity. However, motivation is the largest variable in influencing work productivity, while other variables such as work training and work discipline also show a fairly strong influence. The determination test shows that there is a close relationship between work discipline, work training, and work motivation on employee productivity. This is proven by the R-value of 0.516, which means that work discipline, work training, and work motivation have an effect of around 51.6% on the total employee productivity of PT Sukses Anugerah Sejahtera, while other factors outside this research model influence the rest.